Estudio de factibilidad para la creación de una escuela de protocolo y etiqueta en el cantón Quevedo en el año 2013 - Velastegui Castro, Evelyn Vanessa (2014)
This research was conducted in the Canton Quevedo which has 173575 inhabitants, was to market research, technical, organizational, economic, and financial evaluation projected 5-year term in order to give the investor a tool support for creation of a school of protocol and etiquette, knowing you will never have this type of service in the canton Quevedo by another company. For registration information, a questionnaire was used to survey the citizens of Canton Quevedo criterion to determine its quality and price that they prefer when making use of this service. The net present value had a positive value of $ 71.469.92 which means the liquid return generated by the project update. Therefore the project is feasible The internal rate of return is 47 %, which was higher than the market interest rate; therefore the project is feasible and viable from the economic point of view The cost benefit ratio is determined by dividing net profit for the interest rate of the bank loan; obtaining the indication 1.47.